Solomon's thieves. Book one - Mechner, Jordan (First Second, 2010)
On the run from the law in 14th century France, Templar Knight Martin finds himself one of the only Templars out of prison--and out for revenge! It seems that a vast conspiracy is afoot to destroy the Templar Order and steal their treasure. A swashbuckling story of betrayal, adventure, and an epic swindle.